Одержання високоякісного антифрикційного мастила на базі модифікованої жирнокислотної сировини - Papeikin, Oleksii O.; Venger, Irina O.; Bodachivska, Larysa Yu. (Каталіз та нафтохімія, 2023)
Currently, the highest quality greases are made on the basis of 12-hydroxystearic acid soaps. But over 80 % of the world’s raw material source of this fatty acid - castor oil - is concentrated in South Asia. This prompts grease manufacturers to search for alternative raw materials for the production of greases with high thixotropic properties. The paper demonstrates the possibility of using phosphatide concentrates as components of high-temperature greases. Active groups in their composition– -OH, -NH2, -CONH, -COOH, -PO(OH)2 provide improved protective and tribochemical properties to lubricating compositions, but the existing double bonds impair their antioxidant resistance. Therefore, a technology for chemical modification of phosphatide concentrate by hydroxylation of unsaturated bonds with subsequent saponification and insitu complexation of the lubricating composition has been developed. The physico-chemical properties of the developed complex calcium grease were studied and a comparative analysis of their quality indicators with greases based on 12-hydroxystearic, stearic acids and unmodified phosphatide concentrate was carried out. The synthesized grease is characterized by high mechanical, colloidal stability and high-temperature properties, its upper temperature limit of application, which is established by the method of derivatographic analysis, reaches 180-200 °С. In addition, this thixotropic system is resistant to oxidation, does not cause corrosion of non-ferrous metals and is able to work in contact with water. Phosphorus-containing residues improve the lubricating properties of the synthesized composition without the addition of tribological modifiers and surpass the functional additives contained in the commercial grease Uniol-2. The conducted tests prove the promising application of hydroxylated phosphatide concentrates as components of high-temperature dispersed phases of soap compositions.